IDENTIFICATION OF SOME CONCENTRATION OF VEGETABLE WASTE COMPOST EXTRACTS AND ITS INFLUENCE TO INCREASING NUTRIENT OF CULTIVATED SOILS - Septyani, Ika Ayu Putri; Dalimunthe, Badrul Ainy; Sepriani, Yusmaidar (Jurnal Galung Tropika, 2023)
One source of organic material is vegetable waste. This research aims to identify differences in the chemical properties of compost extracts and their influence on improving the availability of garden soil nutrients. The research was carried out in Rantau Selatan, Labuhanbatu Regency, North Sumatra Province, with an astronomical location of 99O33' East Longitude - 100O22' East Longitude and 01O41' North Longitude - 02O44' North Longitude. The first stage of this research was to investigate differences in compost extract concentrations using the paired t-test statistical test at the 5% level. In the second stage, a Completely Randomized Design (CRD) was used with 3 treatments and 18 replications and continued with the Least Significant Difference (LSL) further test at the 5% level. The research showed that the 1:5 compost extract had higher chemical characteristics such as pH 6.83%, C-Organic 22.5%, N 0.95%, P 0.37%, and K 8.8%. Providing 1:10 compost extract can increase the nutrients in the yard soil, giving the best results and showing nutrient availability such as pH 4.92%, C-Organic 4.11%, N-total 16.3%, P-bray 251.37%, K-dd 10.9%, and KTK 26.34%.